Single-Cell Profiling Reveals Sex, Lineage, and Regional Diversity in the Mouse Kidney - Ransick, Andrew; Lindström, Nils O.; Liu, Jing; Zhu, Qin; Guo, Jin-Jin; Alvarado, Gregory F.; Kim, Albert D.; Black, Hannah G.; Kim, Junhyong; McMahon, Andrew P. (Developmental cell, 2019)
Chronic kidney disease affects 10% of the population with notable differences in ethnic and sex-related susceptibility to kidney injury and disease. Kidney dysfunction leads to significant morbidity and mortality and chronic disease in other organ systems. A mouse-organ-centered understanding underlies rapid progress in human disease modeling and cellular approaches to repair damaged systems. To enhance an understanding of the mammalian kidney, we combined anatomy-guided single-cell RNA sequencing of the adult male and female mouse kidney with in situ expression studies and cell lineage tracing. These studies reveal cell diversity and marked sex differences, distinct organization and cell composition of nephrons dependent on the time of nephron specification, and lineage convergence, in which contiguous functionally related cell types are specified from nephron and collecting system progenitor populations. A searchable database, Kidney Cell Explorer (https://cello.shinyapps.io/kidneycellexplorer/), enables gene-cell relationships to be viewed in the anatomical framework of the kidney. [Display omitted] •Proximal nephron segments show distinct expression profiles between the sexes•The time of nephron formation determines position and segmental cell diversity•Lineage convergence is observed at nephron-collecting system junctions•Data can be queried and viewed within an annotated anatomical database Ransick et al. combined in-depth single-cell profiling of male and female adult kidneys with cluster registration to kidney structures to generate an anatomical atlas of the mammalian nephron and collecting system. Kidney Cell Explorer (https://cello.shinyapps.io/kidneycellexplorer/) enables gene-cell relationships to be viewed in the anatomical framework of the mammalian kidney.